MAE514: Mathematical Software in Education / Faculty of Education - UiTM, Faculty of Education (2023)
This course is designed to interpret students' understanding of mathematical concepts by applying some mathematical software. Students are expected to solve computational problems using technology such as Geogebra / other mathematical software. Emphasis will be given on how to use mathematical software in teaching mathematics. In addition, students also will explore the usage of other mathematics tools such as scientific calculators, google sheets, and excel in explaining mathematical concepts.